Cellulolytic Yeast Isolated From Raja Ampat Indonesia - Kanti, Atit; Sukarno, Nampiah; Sukara, Endang; Darusman, Latifah K. (Annales Bogorienses, 2012)
The objective of this study was to select and characterize three yeast isolates originating from soil of Raja Ampat region of Papua, Indonesia for its potential to produce cellulase . Selection and characterization of cellulolytic yeast was carried out by measuring cellulolytic Index (IS)with congo red method and measurement of Carboxy Methyl Cellulase (CMC-ase) activity through determination of reducing sugar with dinitrosalycilic methods. Cellulolytic Index (IS) of the isolates Sporobolomyces poonsookiae Y08RA07, Rhodosporidium paludigenum Y08RA29, and Cryptococcus flavescens Y08RA33 were 1.40, 2.60 and 1.66, respectively. CMC-ase produced optimum at pH 8 at 37ºC by isolate Y08RA07; whereas for Y08RA29 and Y08RA33 were at pH 6, at 28ºC. Paper waste was good substrate for cellulase enzyme production by isolate Y08RA07, while for two other isolates the best substrate was CMC. Isolate Y08RA29 having highest cellulase activities when grown in CMC, while isolates Y08RA07 and Y08RA33 achieved highest enzyme activity when grown in bamboo leaf.